Analisis Tense Phrase Menggunakan Teori X-Bar pada Kalimat dan Klausa di dalam Teks Recount Bahasa Inggris (Pendekatan Sintaksis) - Adhitya Darmawan (Universitas Sebelas Maret, 2025)
This study presents a comprehensive syntactic analysis of tense phrases within the framework of X-bar theory applied to recount texts. Utilizing a corpus of diverse recount narratives, we employ a generative approach to scrutinize the hierarchical structure and syntactic relationships governing tense constituents. Our investigation reveals intricate patterns of tense phrase formation, shedding light on the underlying syntactic mechanisms that govern temporal information encoding. Through a meticulous examination of tense-related features, we uncover the nuanced interplay between functional projections and lexical elements, offering insights into the syntactic complexities of recount narratives. Furthermore, this research contributes to a deeper understanding of tense phrase structures, providing a foundation for future explorations in syntactic analysis. The findings herein not only advance our comprehension of temporal representation in language but also underscore the significance of X-bar theory in elucidating intricate syntactic phenomena.